HUBUNGAN ASI EKSKLUSIF DENGAN KEJADIAN STUNTING PADA BALITA DI UPTD TELUK SASAH PUSKESMAS TELUK SASAH - Hartati, Eva; Mariyana, Mariyana (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2020)
In 2016, it is estimated that children under five who experience stunting in the world are 22.9%, but this figure has decreased in 2017 by 22.2%, although the incidence of stunting has decreased, but has not reached the standard set by WHO, namely 20 % (Ministry of Health of the Republic of Indonesia, 2019). The purpose of this study was to determine whether there was a relationship between exclusive breastfeeding and the incidence of stunting in children under five in the UPTD of the Teluk Sasah Health Center in 2020. This study used a cross sectional research design carried out at the UPTD of the Teluk Sasah Health Center. In July 2020. The population was all toddlers aged 24-24. 36 months and a sample of 40 people with the Consecutive Sampling sampling technique. From the results of the study, most of the respondents who gave exclusive breastfeeding with normal nutritional status were 73.7%, only 14.3 experienced stunting and most of the respondents did not give exclusive breastfeeding with experienced stunting there were 85.7%, only 26.3% were normal. The results of the chi-square statistical test obtained a p value of 0.000â‰¤0.05. The conclusion is that there is a relationship between exclusive breastfeeding and the incidence of stunting in toddlers at the Teluk Sasah Health Center UPTD 2020. Mother's advice is to pay attention to and increase children's food needs that contain adequate consumption of nutrients.